Differences in Scientific Argumentation Skills of Preservice Physics Teachers in Written and Oral Contexts: A Case Study of Video-Based Microteaching Learning - Gunawan, Gunawan; Herayanti, Lovy (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study aims to analyze the profile of scientific argumentation skills of preservice physics teachers in the context of written case studies and oral presentations through video-based microteaching learning. Data was collected from 15 preservice physics teachers participating in a microteaching course. Qualitative analysis of argumentation components (claim, reason, evidence, rebuttal, conclusion) revealed significant differences in argumentation skills between the two contexts. In written case studies, students demonstrated a relatively good ability to present evidence. However, they needed to improve in formulating claims and reasons. Meanwhile, in oral presentations, there was a significant increase in all components of argumentation, particularly claims, reasons, rebuttals, and conclusions. These findings have important implications for developing more effective microteaching learning to improve the scientific argumentation skills of preservice physics teachers.